Strategi Pengelolaan Sumber Daya Manusia dalam Meningkatkan Mutu Pendidikan Tinggi Vokasi (Studi kasus di Politeknik STIBisnis) - Rhisty Frida Utami; Wiliyanto (Tamilis Synex: Multidimensional Collaboration, 2026)
This study aims to describe in depth the human resource management strategy implemented at the STIBisnis Polytechnic. This study uses a qualitative approach with a case study design to deeply understand the human resource management strategy in the real context of vocational higher education, with the research location at the STIBisnis Polytechnic and purposively selected informants including leaders, lecturers, education staff, and students to obtain a comprehensive perspective. Data were collected through in-depth interviews, participant observation, and documentation studies of the Strategic Plan, HR SOPs, performance reports, accreditation documents, and industrial collaborations to obtain a factual and contextual picture of HR management practices. Data analysis was carried out interactively following the Miles and Huberman model through the stages of reduction, presentation, and conclusion drawing, with validity tests using source triangulation, technical triangulation, and member checking to ensure the credibility of the findings. The results show that the human resource management strategy at the STIBisnis Polytechnic has been designed in an integrated manner with the institution's vision and focuses on improving the quality of vocational education through needs planning, industry-based competency recruitment, and continuous professional development of lecturers. The implementation of a structured performance evaluation system and a collaborative organizational culture has been proven to strengthen the effectiveness of HR policies in improving learning quality, curriculum relevance, and student satisfaction. However, institutions still face challenges in optimizing training based on developments in the digital industry and increasing the number of doctoral-qualified lecturers to strengthen academic competitiveness.